STUDY OF THE POTENTIAL AND FINANCIAL FEASIBILITY OF TIDAL CURRENT POWER AS AN ALTERNATIVE ENERGY POWER PLANT IN CAPALULU STRAIT, NORTH MALUKU - Wahid Siddik, Muhammad
Indonesia with an ocean area of two-thirds of its country needs to explore renewable energy sources, one of which is ocean current energy to meet its electricity needs. The purpose of this reasearch is to determine potential locations and generating instruments that are appropriate to its location and to analyze the selling price of electricity that is economically feasible. In this reasearch, hydrodynamic modeling is needed to determine ocean currents in 3 locations (named: observation 1, 2 and 3). By the input of tidal constituents, obtained the water level and current velocity in each location for a year. Each location gives a water elevation validation less than 10%. From the Capalulu Strait model, there are 2 potential locations (observation 2 and 3). From these two locations, the location with the largest median of current velocity was obtained at the location of observation 2. At that location, 8 GHT is needed with power production in 2020 of 147,75 MWh. In 2020, this project will require an investment of Rp. 15.895.144.249,40 and the required value of the selling price of the electricity is Rp. 4.303 per kWh to return investment for 25 years.